From Illumination to Biological Regulation: A Biological Reappraisal of Lighting Management in Chickens – A Review - Yadi Oktariansyah; Ferta Liza Putri (Jurnal Biologi Tropis, 2026)
Lighting management is a fundamental component of chicken production systems and has traditionally been applied as a technical tool to enhance activity, feeding behavior, and productivity. Increasing evidence, however, indicates that light functions not merely as illumination, but as a key biological signal regulating circadian rhythms, neuroendocrine pathways, behavior, welfare, and long-term production performance. This review provides a biological reappraisal of lighting management in chickens by synthesizing current evidence on how different lighting characteristics influence biological regulation and practical outcomes. A systematic literature review was conducted following PRISMA guidelines, with a qualitative synthesis approach adopted due to heterogeneity in study designs, lighting protocols, and outcome measures. Evidence was integrated across major lighting domains, including photoperiod duration, timing consistency, light intensity, spatial distribution, spectral composition, lighting technology, and stage-specific implementation. Emphasis was placed on identifying primary biological targets, expected production benefits, risks of mismanagement, and relevant monitoring indicators. The synthesized findings demonstrate that lighting management acts primarily through alignment with endogenous circadian and endocrine systems rather than isolated technical parameters. Lighting regimes that preserve circadian stability support sustainable productivity and animal welfare, whereas biologically inappropriate strategies may induce cumulative physiological stress and compromise long-term performance. This review highlights the need to reframe lighting management as a form of biological regulation to support data-driven and biologically informed production systems.